United 93 - Greengrass, Paul; Clemenson, Christian, 1959-; Gates, Trish; Adams, Polly (Universal City, Calif. : Universal, 2006)
Tells the story of the people on United flight 93, one of the four hijacked planes on September 11, 2001, and how they foiled their hijackers' terrorist plot.
Christian Clemenson, Trish Gates, Polly Adams, Cheyenne Jackson, Opal Alladin.
MPAA rating: R.
DVD, Dolby digital 5.1 surround.
In English, French, or Spanish with optional English, French, or Spanish subtitles.
Keywords: United Airlines Flight 93 Hijacking Incident, 2001 -- Drama; September 11 Terrorist Attacks, 2001 -- Drama; Thrillers (Motion pictures, television, etc.); Feature films; Historical films